Blood diseases an essential slide collection - Hewitt, Patricia E.; Gower Medical Publishing Ltd. (London : Gower Medical Publishing, 1989)
Covers a variety of haematological conditions and some of their complications. Clinical photographs are supplemented by radiography and photomicrographs
Keywords: Blood -- Diseases; Hematology; Hematologic Diseases -- slides